2012
DOI: 10.1080/13825585.2011.628377
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of subclinical depression in prospective memory and ongoing tasks in young and old adults

Abstract: Results reported in the literature show that depression can have either negative or neutral effects on prospective memory (PM). The goal of the present study was to broaden the analysis of depression-related effects on PM, with regard to the possibility that subclinical depression may have positive influence on PM. A total of 120 participants from four groups (young/old, subclinically depressed/non-depressed) completed event- and time-based PM tasks embedded in the linear orders task or stories task, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
5
10
0
Order By: Relevance
“…Taken together, these findings suggest that under OI conditions, HDS participants could allocate attentional resources to PM tasks as effectively as LDS participants. These findings are consistent with some previous studies reporting no effect of depression on resource-demanding PM tasks (Albiński et al, 2012;Altgassen et al, 2011) and our earlier finding that was based on the same participants as those that were used in the present study (Li et al, 2013)-that that there were no depression-related event-based PM deficits when using the MIST.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Taken together, these findings suggest that under OI conditions, HDS participants could allocate attentional resources to PM tasks as effectively as LDS participants. These findings are consistent with some previous studies reporting no effect of depression on resource-demanding PM tasks (Albiński et al, 2012;Altgassen et al, 2011) and our earlier finding that was based on the same participants as those that were used in the present study (Li et al, 2013)-that that there were no depression-related event-based PM deficits when using the MIST.…”
Section: Discussionsupporting
confidence: 95%
“…Of the remaining 16%, eight participants with elevated depression screening scores had subsequent scores in the minimal range (HDS to LDS), and two participants with originally minimal symptoms reported elevated symptoms on the second testing (LDS to HDS). BDI-II scores in our HDS cohort (M HDS = 25.75, SD = 9.98; M LDS = 7.72, SD = 3.32) were substantially elevated and similar or greater than the mean BDI-II scores reported in previous studies (Altgassen et al, 2009(Altgassen et al, , 2011Albiński et al, 2012;Chen et al, 2013;Rude et al, 1999). As this was part of a larger study undertaken to investigate the effects of depressive symptomatology, note that the participants in this study were also used in another study using the MIST PM measure (Li et al, 2013).…”
Section: Methods Participantssupporting
confidence: 76%
See 2 more Smart Citations
“…When participants are required to make a PM response to an event embedded in an ongoing task (event-based PM task), one study reported PM impairments as a function of depression (Altgassen et al, 2009), but two others did not (Albiński et al, 2012;Altgassen, Henry, Bürgler, & Kliegel, 2011). To our knowledge, no study has directly compared whether the magnitude of PM deficits associated with depression varies as a function of cue type in a single standardized clinically relevant PM measure.…”
Section: Introductionmentioning
confidence: 94%